2015
DOI: 10.1590/1678-775720140524
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical performance and degree of conversion of resin cements: a literature review

Abstract: Resin-based cements have been frequently employed in clinical practice to lute indirect restorations. However, there are numerous factors that may compromise the clinical performance of those cements. The aim of this literature review is to present and discuss some of the clinical factors that may affect the performance of current resin-based luting systems. Resin cements may have three different curing mechanisms: chemical curing, photo curing or a combination of both. Chemically cured systems are recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
97
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 70 publications
(206 reference statements)
6
97
0
6
Order By: Relevance
“…However, former studies have provided evidence that the activation time generally recommended by the manufacturer is not sufficient to achieve the maximum degree of conversion . Therefore, prolonged light exposure is recommended when highly opaque or thicker restorations are required, because a gradual increase in the light‐curing time and, consequently, light transmission results in a gradual increase in the hardness of resin‐based luting systems . The degree of conversion of a dual‐cure resin cement may vary from 37% when light cured for 20 seconds to 58% when light cured for 40 seconds; this confirms the aforementioned direct correlation between the light intensity received by a photoactivated dual‐cure material and its degree of conversion …”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…However, former studies have provided evidence that the activation time generally recommended by the manufacturer is not sufficient to achieve the maximum degree of conversion . Therefore, prolonged light exposure is recommended when highly opaque or thicker restorations are required, because a gradual increase in the light‐curing time and, consequently, light transmission results in a gradual increase in the hardness of resin‐based luting systems . The degree of conversion of a dual‐cure resin cement may vary from 37% when light cured for 20 seconds to 58% when light cured for 40 seconds; this confirms the aforementioned direct correlation between the light intensity received by a photoactivated dual‐cure material and its degree of conversion …”
Section: Discussionmentioning
confidence: 55%
“…It is expected that the tertiary amine will interact with benzoyl peroxide to secure adequate curing in areas with inadequate light exposure. However, it has been reported that dual‐cure resin cements may perform decreased hardness when not properly photoactivated, which implies a reduced degree of conversion . In this study, it was observed that Panavia F 2.0 was not polymerized under 2.5‐mm‐thick monolithic zirconia and 3‐mm‐thick monolithic lithium disilicate, whereas the other two cements were polymerized under all ceramic thicknesses.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It must be considered that the adhesion of the restoration is dependent on the type of cement used moreover, it can be expected that the greater the adhesion of the restoration, the better the stress distribution within the system, thus resulting in higher fracture resistance. Not less important, premolars and molars may receive similar forces during oral function, contributing for the similar results when considering only posterior teeth [53]. Forberger et al [54] endocrowns resulted in similar fracture strength when compared to groups restored with posts based on ceramic (zirconia), gold or glass fiber.…”
Section: Discussionmentioning
confidence: 90%